Groundwater Characteristics Analysis to Identify the Seawater Intrusion in Coastal Deep Aquifer System, Semarang, Central Java, Indonesia - Listiawan, Yudhi; Virgianty, Aisyah Shafa; Pramudyo, Tulus; Iskandarsyah, Teuku Yan Waliana Muda (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The study area is located in Semarang, representing a coastal and industrial zone where groundwater exploited as main water resources. Seawater instrusion has been identified as a significant issue in coastal regions due to its impact on groundwater quality. The study was conducted using groundwater data from deep aquifers (bore wells). The physical and chemical contents were analyzed to determine the groundwater characteristics and identify the seawater intrusion. Piper and Durov diagram were used to determine the hydrochemical facies and the main processes that influence the chemical content in groundwater. The Cl vs Na/Cl ratio diagram were used to identify the source of Cl and Na ions, determining weather the ions originate from anthropogenic activites or seawater intrusion. The Physical properties of groundwater show that the groundwater in the study area is divided into 2 group: a freshwater group with TDS value <1000 mg/L and a brackish water group with TDS value ranging from 1000 – 4006 mg/L. The results of hydrochemical analysis indicates the occurrence of seawater intrusion in some locations. Seawater intrusion in the study area mainly occurs in the northern part of Semarang city which relatively near with coastal line. The seawater intrusion also occurs in the eastern part of study area (Demak) with a more severe level, reaching areas at a further distance from coastal line compared to Semarang city.